Swallowing disorders in relation to brain localization - Zelic, Mirna; Todorović, Jelena; Pavlovic, Dragan (Acta medicae Medianae, 2021)
Swallowing disorders (dysphagia) include both difficulty in swallowing and controlling saliva and difficulty in feeding. These disorders affect all age groups from newborn to old, and  they could lead to congenital abnormalities, damage to the anatomical structures they use to swallow, and various medical things can be present. Dysphagia may be acute (e.g., possibly stroke) or may progress over time (e.g., tumors and progressive neurological diseases). Numerous regions are involved in act of swallowing which include precentral gyrus, postcentral girus, premotor zone, complementary motor zone, operculum, insula, precuneus, prefrontal arena, temporal lobe, cerebellum, brainstem, frontal lobe, capsule-internal, capsule- u-internal fields, thalamus and basal ganglia. Understanding the process of swallowing is crucial to further plan for an adequate approach to the treatment of this function disorder.
Keywords: dysphagia, swallowing disorders, possibly lesions, pathophysiology of swallowing, dysphagia therapy